Synsepalum dulcificum extracts exhibit cytotoxic activity on human colorectal cancer cells and upregulate c-fos and c-jun early apoptotic gene expression - Jichang Seong; Glenn G Oyong; Esperanza C Cabrera (Asian Pacific Journal of Tropical Biomedicine, 2018)
Objective: To explore cytotoxicity of Synsepalum dulcificum (S. dulcificum) Daniell (Sapotaceae) on human colon cancer (HCT-116 and HT-29), human monocytic leukemia (THP-1) and normal (HDFn) cell lines, and its effect on the expression of early apoptotic genes, c-fos and c-jun. Methods: Leaf, stem and berry of S. dulcificum were separately extracted by using 2 solvents, 10% ethanol (EtOH) and 80% methanol (MeOH). PrestoBlue® cell viability assay and qRT-PCR assay were conducted to examine the above objectives respectively. Results: Stem MeOH, stem EtOH, and berry EtOH extracts of S. dulcificum were cytotoxic to HCT-116 and HT-29 human colon cancer cells. For HCT-116, IC50 values of these 3 extracts were not significantly different (P>0.05) from that of the positive control bleomycin (IC50 of 33.57 μg/mL), while for HT-29, IC50 values of these 3 extracts were significantly lower (P<0.05) than that of bleomycin (IC50 of 25.24 μg/mL). None of the extracts were cytotoxic to the THP-1 monocytic leukemia cells and HDFn normal human dermal fibroblasts. For both HCT-116 and HT-29, these extracts significantly up-regulated (P<0.05) the expression of c-fos and c-jun compared to the untreated negative control. Conclusions: The results of this study suggest that cytotoxicity of stem MeOH, stem EtOH, and berry EtOH extracts of S. dulcificum on HCT-116 and HT-29 colon cancer cells is due to the induced apoptosis which is caused by the up-regulation of the expression of early apoptotic genes, c-fos and c-jun.